The development of low‐calorie sugar and functional jujube food using biological transformation and fermentation coupling technology. Issue 4 (6th March 2019) - Men, Yan; Zhu, Ping; Zhu, Yueming; Zeng, Yan; Yang, Jiangang; Sun, Yuanxia
Abstract: Jujube juice has been used as ingredient in a range of foods and dietary supplements. In this study, an enzyme transformation and fermentation coupling technology was applied to increase the nutritional value of concentrated/extracted Jinsi jujube juice. Two enzymes, D‐glucose isomerase (GI) and D‐allulose 3‐epimerase (DAE), were employed to convert the glucose and fructose to a low‐calorie sweeter D‐allulose with a concentration of 110 g/L in jujube juice. Furthermore, the mixed cultures of Pediococcus pentosaceus PC‐5 and Lactobacillus plantarum M were employed to increase the content of nutrition components related to bioactivities and flavor volatiles in jujube juice. Accordingly, this fermentation accumulated 100 mg/L gamma‐aminobutyric acid (GABA), which has neurotransmission, hypotension, diuretic, and tranquilizer effects, and increased the content of branched‐chain amino acids (BCAAs) and many free amino acids (Asp, Glu, Gly, and Ala) at different level. The fermentation not only maintained the concentration of native functional components such as cyclic adenosine monophosphate (cAMP) and minerals, but also increased the content of iron (Fe 2+ ) and zinc (Zn 2+ ), which have blood and eyesight tonic function. The value‐added jujube juice might serve as a low‐calorie and probiotic functional beverage and show high application potential in food industry. Abstract : An enzyme transformation and fermentation coupling technology was applied to increase the nutritional value of concentrated/extracted Jinsi jujube juice. The value‐added jujube juice might serve as a low‐calorie and probiotic functional beverage and show high application potential in food industry.